IN VITRO FLOW ANALYSIS OF NOVEL DOUBLE-CUTTING, OPEN-PORT, ULTRAHIGH-SPEED VITRECTOMY SYSTEMS. Issue 12 (December 2018) - Zehetner, Claus; Moelgg, Marion; Bechrakis, Emmanouil; Linhart, Caroline; Bechrakis, Nikolaos E.
Abstract : Purpose: To analyze the performance and flow characteristics of novel double-cutting, open-port, 23-, 25-, and 27-gauge ultrahigh-speed vitrectomy systems. Methods: In vitro fluidic measurements were performed to assess the volumetric aspiration profiles of several vitrectomy systems in basic salt solution and egg white. Results: Double-cutting open-port vitrectomy probes delivered stable aspiration flow rates that were less prone to flow variation affected by the cutting speed. Increase in cutting frequency to the maximum level resulted in flow reduction of less than 10% (0.0%–9.5%). Commercially available 23-, 25-, and 27-G double-cutting probes exhibited higher egg-white and basic salt solution flow rates at all evaluated cut rates, with aspirational efficiencies being 1.1 to 2.9 times the flow rates of standard single-blade vitrectomy probes of the same caliber at the maximum preset vacuum. The highest relative differences were observed at faster cut rates. Conclusion: The newly introduced double-cutting open-port vitrectomy probes delivered stable aspiration flow rates that were less prone to flow variation affected by the cutting speed. The fluidic principle of constant flow even at the highest cut rates and low vacuum levels might impact surgical strategies, especially when performing manipulations close to the retina. Abstract : The authors performed in vitro measurements to determine the fluidic performance of novel double-cutting, open-port, 23-, 25-, and 27-gauge ultrahigh-speed vitrectomy probes. Commercially available double cutters had higher aspirational flow than standard vitrectomy probe designs of the same caliber. The highest relative differences were observed at faster cut rates.